Turkey and the Black Sea Economic Cooperation: Opportunities and Challenges - Gamawa, Yusuf Ibrahim (American Economic & Social Review, 2018)
This paper aims to analyse Turkey’s relationship with other states in the Black Sea region, and takes a look at reasons behind the formation of the Black Sea Economic Cooperation that was spearheaded by Turkey. The paper also highlights the importance of the region and the struggle by outside powers for influence in the region. These powers include Russia and the United states, alongside Turkey.